Psychosocial Issues and Sources of Support Affecting Retention for Adult Learners: Generational Variations - Debbie Ritter-Williams; Ruby A. Rouse (Adult Education Research Conference, 2011)
Amid predictions of increasing numbers of jobs requiring employees with degrees, the retention of adult students returning to degree programs has become a critical concern. This study investigates generational differences in psychosocial factors that may influence adult students to discontinue taking classes, and the sources of support they find most helpful and important. A newly- created survey instrument was found to have acceptable validity and reliability and used to collect data from thousands of adult college students in April-May 2011.
Keywords: adult; retention; psychosocial; generational; support